Stability of edge magnetism in functionalized zigzag graphene nanoribbons. (November 2017) - Shinde, Prashant P.; Gröning, Oliver; Wang, Shiyong; Ruffieux, Pascal; Pignedoli, Carlo A.; Fasel, Roman; Passerone, Daniele
Abstract: Graphene nanoribbons are attractive candidates for future technological applications due to exceptional electronic and magnetic properties. We investigate the stability of edge magnetism in zigzag graphene nanoribbons with indene-type functionalized edges, recently synthesised on Au(111) in our laboratory. Using density functional theory (DFT) calculations, we show that the functionalized nanoribbons preserve most electronic properties of the pristine ribbon, with band modifications making edge magnetism sensitive or unstable to environmental influences. The tendency towards such instability already emerges when the system is investigated with a simple mean field Hubbard model where the on-site Coulomb repulsion can be parametrically tuned. It becomes fully evident in DFT calculations when the mostly dispersive interactions between the nanoribbon and the metal substrate are modeled using different van der Waals correction schemes. One of such schemes gives results in agreement with spectroscopy experiments in which the highest occupied and lowest unoccupied states locate on the unmodified and modified zigzag edge sections, respectively. When a different dispersion correction approach is considered, theory predicts, despite a very similar adsorption geometry, an inversion of occupied/unoccupied states and a 60% reduction in absolute magnetization. Such sensitivity with respect to small perturbations is discussed. Graphical abstract: